Effectiveness of board governance and dividend policy as alignment mechanisms to firm performance and CEO compensation - Farzan Yahya; Zahiruddin B. Ghazali (Cogent Business & Management, 2017)
Purpose: The purpose of the study is to investigate whether operating and market performance are aligned to CEO compensation and how board governance and dividend policy could influence pay–performance link in the capital market of Pakistan. Design/methodology/approach: The hand-collected information on 219 non-financial firms listed on the Pakistan stock exchange (PSX) is acquired over the period 2012–2016. Additionally, panel data technique, namely Prais–Winsten (PCSE) and 2SLS (robust standard errors) regression are applied to account for the heteroscedasticity, serial correlation and endogeneity issue. Findings: The empirical results indicate that CEO compensation is positively associated with operating performance and market performance. The evidence also provides partial support to agency perspective that board independence and optimal board size could positively, while CEO duality negative moderates the relationship between operating performance and CEO compensation. However, none of these mechanisms are proved to be effective in aligning market performance to CEO compensation. In fact, dividend policy negatively moderates the association between firm performance (operating and market) and CEO compensation. Thus, contrary to the agency theory's proposition, dividend policy cannot be utilized as a substitute control device in the absence of strong corporate governance mechanisms. Practical Implications: In light of this empirical evidence, regulatory bodies in Pakistan could improve corporate governance mechanisms as well as CEO compensation structure to ensure remunerative and ethical financial market. Originality/value: This study contributes to the academic literature by validating the underexplored pay–performance alignment propositions of agency theorists, especially in the reference of Pakistan.
Keywords: 650